2003
DOI: 10.1124/dmd.31.6.755
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Cyp3a Expression in Human Liver Suggests Only a Minor Role for Cyp3a5 in Drug Metabolism

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:To study mechanisms behind the interindividual variability in CYP3A expression and the relative contribution of the different CYP3A enzymes to the overall CYP3A activity, we have analyzed CYP3A4, CYP3A5, CYP3A43, and PXR mRNA and CYP3A4 and CYP3A5 protein expression, catalytic activity, and polymorphism in the CYP3A5 gene in a panel of 46 Caucasian human livers. Protein quantification was performed by Western blotting using enzymespecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
144
4
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(158 citation statements)
references
References 33 publications
7
144
4
3
Order By: Relevance
“…20 Recently, Westlind-Johnsson et al 21 reported that CYP3A5 did not contribute to total CYP3A activity using CYP3A5 polymorphism and nifedipne pharmacokinetics 22 Although these data seem to support the present findings in vivo, the same was not consistent in the case of midazolam. Based on all these observations, we speculated that the amount of CYP3A5 protein in the liver is much lower than CYP3A4, although we should consider the limitations of our study design.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…20 Recently, Westlind-Johnsson et al 21 reported that CYP3A5 did not contribute to total CYP3A activity using CYP3A5 polymorphism and nifedipne pharmacokinetics 22 Although these data seem to support the present findings in vivo, the same was not consistent in the case of midazolam. Based on all these observations, we speculated that the amount of CYP3A5 protein in the liver is much lower than CYP3A4, although we should consider the limitations of our study design.…”
Section: Discussioncontrasting
confidence: 56%
“…25 Interestingly, we have found that mRNA expression of wild-type hPXR is well correlated with mRNA expression of CYP3A4 in liver sample (unpublished data), which is consistent with the recent report. 21 In summary, we revealed that nifedipine disposition in vivo is not affected by the CYP3A5*3 allele. Owing to a discrepancy between the in vitro and in vivo contribution of CYP3A5, the functional relevance of CYP3A5 in humans should be re-evaluated by clinical studies for each drug.…”
Section: Discussionmentioning
confidence: 87%
“…For example, recent data on the relative expression levels of CYP3A4 and CYP3A5 have remained controversial. [11][12][13] Similar problems persist for other larger subfamilies including CYP2C and CYP4F.…”
Section: Introductionmentioning
confidence: 94%
“…CYP3A5 is considered to be 17-50% of the total CYP3A content in the livers of people that express it. 25,26 There is considerable intra-and interindividual variation in CYP3A4 enzyme activity, and even though numerous polymorphisms have been found, the molecular basis of this is not yet understood. On the other hand, CYP3A5 exists in distinct fast and slow variants, 25 and is therefore worth studying even if it is less abundant than CYP3A4.…”
Section: Introductionmentioning
confidence: 99%